Development of a Content Management System (CMS) for Mathematics Learning Tools Of Mathematics Pre Service Teachers - Etika Khaerunnisa; Isna Rafianti; Aan Subhan Pamungkas; Heni Pujiastuti; Yani Setiani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
The teacher has an important role in efforts to achieve the learning objectives of the students. In an effort to achieve the learning objectives, the teacher must prepare learning plans that refer to the content standards and learning objectives in each subject. How important is a mathematical learning plan, so that prospective mathematics teachers need to be equipped with the ability to arrange learning tools during lectures. To encourage the skills of prospective teachers in compiling learning tools, one alternative is to integrate TIK. The development of Wordpress Content Management System (CMS) as a learning media is expected to be a learning resource that can be accessed by prospective mathematics teacher students without limited space and time in developing mathematics learning tools which include annual programs, semester programs, syllabus, Learning Implementation Plans (RPP), Student Worksheets (LKS), with the aim of producing a product in the form of learning media that utilizes WordPress Content Management System (CMS) with mathematical learning device content. The research method used is Research and Development (R & D). The research procedure includes seven steps, namely: potential and problems, data collection, product design, design validation, design revision, product testing, and product revision. The instruments used were questionnaires, namely questionnaires for material experts, for media experts, and questionnaires used for limited testing to prospective mathematics teachers in this case students in the mathematics education department at Untirta. the results of the assessment of experts and respondents is equal to 83,8%, meaning that they have met the indicators of success of the products developed.